Statins for Patients Undergoing Thoracic Aortic Aneurysm Repair Surgery: What to Do? - Klein, Katherine M.; Jovin, Ion S. (AORTA, 2021)
Statins may be associated with improved outcomes in patient with thoracic aortic aneurysms but there is little data on the role of statins in patients who have undergone thoracic aortic aneurysm repair.
Keywords: statins; thoracic aortic aneurysm; aneurysm repair; outcomes